(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Climate change is reshaping species geographic ranges, bringing previously allopatric taxa into secondary contact and generating novel hybrid zones whose dynamics differ fundamentally from historically established zones. This study characterised seven climate-induced hybrid zones in European and Central Asian mammalian species pairs spanning three orders (Carnivora, Rodentia, Lagomorpha), all formed or substantially expanded within the last 50 years, using whole-genome SNP data (RADseq; 286 individuals; mean 12,484 SNPs) combined with historical museum specimen georeferencing and species distribution modelling to quantify zone formation timing, current width, and genomic admixture architecture. All seven zones were confirmed as recent (<50 years) based on museum record absence of pre-1970 sympatry and SDM non-overlap under pre-2000 climate data. Current zone widths ranged from 18 to 284 km, strongly negatively correlated with cline steepness (r(S) = -0.84, p = 0.018). ADMIXTURE identified F1-F3 hybrids at all seven zones, with hybrid frequency ranging from 4.8% to 28.4%. FST outliers were significantly enriched for thermoregulation (6.8x) and immune function (5.4x) loci, suggesting differential sharing of climate-adaptive variation across hybridising lineages. Bayesian cline analysis confirmed bimodal hybrid zone structure in five of seven cases, consistent with tension zone dynamics. These results demonstrate that climate-induced hybridisation is actively generating genomic novelty through admixture of previously isolated adaptive gene pools, with significant implications for EU Habitats Directive management.